2020
DOI: 10.2147/copd.s253812
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Long-Term Burden of COPD Exacerbations During Maintenance Therapy and Lung Function Decline</p>

Abstract: Introduction Early identification of preventable risk factors of COPD progression is important. Whether exacerbations have a negative impact on disease progression is largely unknown. We investigated whether the long-term occurrence of exacerbations is associated with lung function decline at early stages of COPD. Methods Patients diagnosed with mild/moderate COPD (obstruction and FEV 1 % predicted 50–90%), aged ≥35 years, and a smoking histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…51 The NICE guidelines also recommend short-term OCS use (typically 5 days) in all people admitted to hospital with an exacerbation of COPD (if no contraindications) and to consider their use in community settings when an exacerbation is associated with "a significant increase in breathlessness that interferes with daily activities". 13 OCS can be associated with significant side effects in both the short and long term. 93 Quality Standard 4: Appropriate Follow-Up…”
Section: Regularly Assess Inhaler Choice and Technique: Whilementioning
confidence: 99%
See 1 more Smart Citation
“…51 The NICE guidelines also recommend short-term OCS use (typically 5 days) in all people admitted to hospital with an exacerbation of COPD (if no contraindications) and to consider their use in community settings when an exacerbation is associated with "a significant increase in breathlessness that interferes with daily activities". 13 OCS can be associated with significant side effects in both the short and long term. 93 Quality Standard 4: Appropriate Follow-Up…”
Section: Regularly Assess Inhaler Choice and Technique: Whilementioning
confidence: 99%
“… 12 Furthermore, patients who experience a greater exacerbation burden after initiation of maintenance therapy have worse lung function at diagnosis and a more rapid lung function decline thereafter, emphasizing the need for better treatment strategies. 13 These findings highlight the importance of earlier intervention among patients with COPD, to more proactively diagnose and manage optimally. Current gaps in COPD management and the need for improved quality of care have been recognized both in the UK and the USA.…”
Section: Introductionmentioning
confidence: 98%
“…[29][30][31][32] For instance, many people diagnosed with COPD are not prescribed maintenance inhaled therapy, despite evidence that this reduces the exacerbation risk in some patients. 12,41 Of those receiving treatment, up to three-quarters of people that experience two or more exacerbations continue to be undertreated according to GOLD recommendations. 42 Halpin et al reported that only between 33% and 60% of patients are treated appropriately according to GOLD recommendations.…”
Section: Act On Exacerbations: Review and Reduce Action Pointmentioning
confidence: 99%
“…1,3 Patients who experience more exacerbations after starting maintenance inhaled therapy show a particularly rapid decline in lung function. 12 The time between exacerbations shortens with more frequent exacerbations. 1 Exacerbations seem to cluster, which partly accounts for the high hospital readmission rates.…”
Section: Introductionmentioning
confidence: 99%
“…It is a significant public health problem worldwide with an estimated prevalence between 11 and 26% in the BOLD Study Document "International variation in the prevalence of COPD". It is also a significant cause of hospitalizations and mortality, placing a high burden on healthcare systems [2][3][4][5][6] . These hospitalizations represent the single largest source of expenditure on patients with COPD 7 .…”
Section: Introductionmentioning
confidence: 99%